The folding cliffs a narrative - Merwin, W. S. 1927-2019 (Knopf, 1998)
Pursued by colonial troops, a family in 19th century Hawaii flees into the interior to avoid internment as lepers. Written in verse, the novel looks at the destruction of an indigenous culture.
Keywords: Geschichte 1800-1900; Hawaii -- Motiv; Lyrik; Hawaii -- Poetry